Basidial mushrooms as indicators of natural ecosystem pollution - Korolchuk, O.V.; Vitriak, O.P.; Reshetniak, L.R. (Problems of Environmental Biotechnology, 2021)
Samples of basidiomycetes of the natural forest ecosystem near the lake Diamond in Desnyansky district of Kyiv were studied to detect the accumulation of heavy metals. The ecosystem is located close to the anthropogenic source of pollution - CHP-6. It was found that the maximum amount of heavy metals accumulated in Boletus edulis and Lycoperdon perlatum, the minimum - in Cantharellus cibarius, which exceeds the MPC and the hazard factor (Fh). It is proved that basidiomycetes can be used as indicators of the state of the environment in soil bioremediation technologies.